PENGENALAN METODE EMBER TUMPUK SEBAGAI UPAYA PENGOLAHAN SAMPAH ORGANIK RUMAH TANGGA DI KAWASAN PERKOTAAN - Sanjaya, Muhammad Fahyu; Suyono, Suyono; Rusmidin, Rusmidin; Mahendra, Yusril (Universitas Mataram, 2024)
Household waste is still a serious problem for environmental quality. Household waste that is not managed properly and correctly causes pollution to the surrounding environment such as unpleasant odors and clogging irrigation in residential areas. The aim of carrying out this service is to increase public knowledge and awareness of processing household waste or organic waste using an environmentally friendly method, namely stacked buckets in urban areas. The partners of this service are the community in the Lipu Environment, North Labuang Subdistrict, West Sulawesi Province. The method used in this service activity is descriptive analysis with a qualitative research type with a case study design. Questionnaires are used to measure community knowledge and awareness before activities are carried out and after activities are carried out. The results of the service show that many people in the Lipu neighborhood are still not aware of the importance of processing household organic waste. This can be seen from direct interactions with the community and the results of the pre-test questionnaire. Furthermore, after carrying out activities to introduce household organic waste processing using the stacked bucket method, the results showed an increase in community knowledge, behavior and awareness in managing household waste. These results provide the community with the ability to manage waste using the 3R process (Reuse, Recycle and Reduce) with the results of the processing being able to be used for cultivating organic vegetable crops in urban areas and can be a solution to environmental pollution problems in the Lipu area of Majene Regency. The implementation of this training succeeded in increasing public awareness of processing their own organic waste using the stacked bucket method. This activity also succeeded in increasing knowledge, behavior and availability of community facilities to support household organic waste processing.